Comparison of weight loss and adverse events of obesity drugs in children and adolescents: a systematic review and meta-analysis. Issue 9 (2nd September 2022) - Zhao, Guangming; Zhang, Qi; Wu, Fan; Yin, Shuang; Xie, Yiqi; Liu, Hongyan
ABSTRACT: Background: The global incidence of childhood obesity is increasing. Currently, there are only few established drugs for treating adolescent obesity. Randomized clinical trials (RCTs) comparing pharmacological interventions in children with obesity are scarce; therefore, we aimed to analyze the relative efficacy and adverse reactions of these drugs and compare the effects of each drug on body mass index (BMI). Research design and methods: This meta-analysis focused on the slimming effect, safety, and correlation of metformin, orlistat, exenatide, liraglutide, and topiramate in children with obesity. Several international databases were searched and clinical trials on the treatment of obesity in children in which the drug was administered for ≥ 6 months were included. Changes in BMI before and after treatment were analyzed using a Bayes framework, and the surface under the cumulative ranking was calculated. Results: Of 2102 relevant articles retrieved, 21 RCTs were included in the study. Compared to other drugs, liraglutide reduced BMI the most in children with obesity. However, it was most associated with drug withdrawal due to adverse events while topiramate was least. Conclusions: Liraglutide had a higher probability of achieving clinically significant weight loss compared with other drugs while topiramate was superior in safety.